Investigating the Causes of Pavement Distresses on Bwankosya Road in Kabale Municipality. - Kigenyi, Luke (Kabale University, 2023)
Flexible pavement defects and their causes are defined in terms of decrease in serviceability which is caused by the development of different types of deteriorations like cracks, surface defects, and disintegration on the flexible pavement. The purpose of this study was to investigate the causes of pavement defects, and provision of remedies to improve the various failures of the surface. This case study attempts to identify the various parameters that affect the performance of the flexible pavement and by rid of this problem by applying the remedial measures over the particular stretch. The road section from Christ the King Church main gate to the old Kabale CPS was chosen as a case study stretching up to 500m. To achieve this aim, the road section was divided into 5 equal sections of 100m. The various defects were measured and their and their corresponding severity and extent levels recorded. Traffic survey was carried out to determine the traffic class along the section, field tests such as the DCP test was carried out to determine the strength and thickness of the pavement layers and materials were tested for suitability in terms of strength in comparison to the specifications. The above tests and surveys were done to identify the causes of the pavement failures and it was found out that most of the pavement sections were damaged by alligator cracks caused by repetitive heavy loading by the vehicles and also due to poor drainage, inadequate designing and poor quality of the base material.